Role of political elites in Iran-Saudi economic cooperation - Amiri, Reza Ekhtiari; Ku Samsu, Ku Hasnita (Center for Promoting Ideas, 2011)
Iran and Saudi Arabia cooperated with each other in 1999 on oil quota and price within the Organization of Petroleum Exporting Countries (OPEC) for the first time since 1979. With regard to the originality of this cooperation, this paper sets out to examine the role of political elites of the two countries in the cooperation. The paper concludes that President Hashemi Rafsanjani and Khatami from the Iranian side and Crown Prince Abdullah from the Saudi side were the key figures who paved the political way for economic cooperation. In other words, in light of the strained Iranian-Saudi relations during the 1980s, their main role was to reduce the tension between the two parties and instead improve mutual political relations during the 1990s, which was a necessary requirement for economic cooperation.